Battery cell and preparation method thereof
During the battery cell preparation process, the catalyst precursor solution is injected and the current or negative voltage is applied to form a catalyst, which solves the problems of complex and high cost of catalyst preparation process in the prior art, and realizes the potential window and improves battery performance. Effect.
Patent Information
- Application Number
- CN202411419685.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-11
AI Technical Summary
In the prior art, the catalyst preparation process required to reduce the potential window of lithium supplement agent is complex and costly.
By injecting the catalyst precursor solution into the encapsulated battery cell and applying a current or a negative voltage after being left to stand, the catalyst precursor is moved in a direction under the action of an electric field force and attached to the surface of the positive electrode sheet to form a catalyst.
The chemical potential window is reduced by 0.3~0.8V, simplifying the catalyst preparation process, reducing costs, and improving the actual capacity and energy density of the battery.
Smart Images

Figure SMS_8
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage battery cells, and in particular to a battery cell and a preparation method thereof. Background Art
[0002] Lithium supplements can improve the performance of battery cells. However, current lithium supplements require a higher potential window to fully release lithium ions, thereby causing a certain degree of electrolyte decomposition, which in turn has a certain impact on the performance of the battery.
[0003] At present, the conventional method to solve the above problems is to synthesize a catalyst that promotes the decomposition of the lithium supplement agent separately, and then mix the synthesized catalyst with the lithium supplement agent (lithium-rich material) to form a lithium supplement material. Although such a scheme can reduce the potential window required for the lithium supplement agent to a certain extent, the synthesis process of the catalyst is cumbersome and the high-temperature synthesis steps involved make the synthesis process of the catalyst complex and costly. Therefore, it is urgent to develop a method that can both reduce the potential window required for the lithium supplement agent and simplify the synthesis process of the catalyst. Summary of the invention
[0004] The main purpose of the present invention is to provide a battery cell and a preparation method thereof, so as to solve the problems in the prior art that the preparation process of the catalyst required to reduce the potential window of the lithium supplement agent is complicated and the cost is high.
[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a battery cell is provided, comprising: stacking a positive electrode sheet, a negative electrode sheet and a separator into a stacked battery cell, and then sequentially performing pole ear welding, packaging, liquid injection, chemical formation and vacuum sealing on the stacked battery cell to obtain a battery cell, wherein the positive electrode sheet is obtained by coating a positive electrode slurry on a positive electrode collector and then drying and laminating, and the positive electrode slurry comprises a positive electrode active material and a lithium supplementer. After packaging and before liquid injection, the preparation method further comprises a catalyst preparation step, and the process of the catalyst preparation step comprises: sequentially injecting a catalyst precursor solution into the battery cell obtained after packaging, standing treatment, applying current or voltage treatment to the battery cell after standing, and removing the catalyst precursor solution; the process of applying current or voltage treatment to the battery cell after standing causes the catalyst precursor to react and adhere to the surface of the positive electrode sheet to form a catalyst; the voltage range is -2.5~0 V.
[0006] Furthermore, the voltage is applied for a time of 0.1 to 12 h; or the current density is in the range of 0.5 to 50 mA·cm -2 The time for applying current density is 0.1~12h.
[0007] Furthermore, compared with the process of packaging, liquid injection and formation of the battery cell in sequence after the tab welding, the process of packaging, catalyst preparation steps, liquid injection and formation of the battery cell in sequence after the tab welding reduces the formation potential window by 0.3~0.8V.
[0008] Furthermore, based on the metal ions in the catalyst precursor solution, the total molar concentration of the catalyst precursor solution is .
[0009] Furthermore, the mass ratio of the above catalyst to the lithium supplement agent is 1:99~30:70.
[0010] Furthermore, the mass concentration of the above-mentioned lithium supplement agent in the positive electrode slurry is 2~3%, and the lithium supplement agent is preferably selected from any one or more of Li5FeO4, Li2NiO2, Li4SiO4, Li2C4O4, and Li2C2O4.
[0011] Furthermore, the above-mentioned catalyst precursor solution includes a catalyst precursor and a first solvent, and / or the electrolyte used for injection includes a second solvent; the step of removing the catalyst precursor solution includes: pouring out the catalyst precursor solution remaining after the reaction, and injecting the third solvent into the battery cell to sequentially soak the battery cell and then pour out the solution after the soaking treatment for cleaning; preferably 2 to 3 cleaning processes are performed, and the time for each soaking treatment is preferably 0.5 to 1 hour; the first solvent, the second solvent and the third solvent are the same type of solvents.
[0012] Furthermore, the catalyst precursor is a compound of metal A, and metal A is selected from any one or more of Mo, W, V, Fe, Co, Ni, Mn, Cr, Cu, Zn, Ce, Bi and In; preferably, the compound of metal A is selected from any one or more of metal A halides, metal A nitrates, metal A phosphates, metal A acid salts and metal A complex salts; preferably, the compound of metal A is selected from CoCl2, MnCl2, Fe(NO3)3, WCl6, VCl3, Ni(NO3)2 and Li2CuCl4. Any one or more; and / or the compound of metal A is a combination of CoCl2 and MnCl2, calculated as metal ions, preferably the molar ratio of CoCl2 and MnCl2 is 2:1~5:1; and / or the compound of metal A is a combination of Fe(NO3)3 and WCl6, calculated as metal ions, preferably the molar ratio of Fe(NO3)3 and WCl6 is 2:1~5:1; and / or the compound of metal A is a combination of VCl3 and Ni(NO3)2, calculated as metal ions, preferably the molar ratio of VCl3 and Ni(NO3)2 is 1:2~1:5.
[0013] Furthermore, the battery cell is subjected to current or voltage treatment for multiple times after being left to stand. Preferably, the number of times of applying current or voltage is 2 to 5 times, and the current range of each application is 20 to 50 mA·cm -2 , the range of each applied voltage is -1.5~0 V; and / or the static treatment temperature is 50~60℃, and the static treatment time is 12~24 h.
[0014] According to another aspect of the present invention, a battery cell is provided. The battery cell is prepared by the above-mentioned preparation method.
[0015] Applying the technical solution of the present application, the preparation method of the battery cell of the present application, after the battery cell is put into the shell, the catalyst precursor solution is injected after the battery cell is packaged, and the catalyst precursor solution is left to stand so that it can fully infiltrate the positive electrode plate, and then the current or negative voltage (such as -2.5~0 V, further, the negative voltage can be -2.5 V, -2 V, -1.5V, -1.0V, -0.5V or 0 V, but not limited to the listed values, other unlisted values within the numerical range are also applicable) is applied to the battery cell after standing, so that the precursor moves in a directional manner under the action of the electric field force through the applied negative voltage or current, and is reduced (oxidized) and loaded on the surface of the positive electrode plate to form the required catalyst. The catalyst interacts with the lithium supplement agent, and its surface has a certain adsorption energy, which can change the reaction pathway, reduce the reaction activation energy, and then catalyze the lithium delithiation reaction of the lithium supplement agent during the formation, thereby not only reducing the lithium delithiation potential window, reducing the decomposition of the electrolyte, but also improving the performance of the battery. Furthermore, the above method of the present application cleverly makes the synthesis process of the catalyst compatible with the preparation process of the battery cell, thereby eliminating the equipment and process for preparing the catalyst separately, thereby simplifying the preparation process of the catalyst and reducing the cost. DETAILED DESCRIPTION
[0016] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0017] As analyzed in the background technology of the present application, the prior art has the problem that the preparation process of the catalyst required to reduce the potential window of the lithium supplement agent is complex and the cost is high. In order to solve this problem, the present application provides a battery cell and a preparation method thereof.
[0018] In a typical embodiment of the present application, a method for preparing a battery cell is provided, comprising: stacking a positive electrode sheet, a negative electrode sheet and a separator into a stacked battery cell, and then sequentially performing pole ear welding, packaging, liquid injection, chemical formation and vacuum sealing on the stacked battery cell to obtain a battery cell, wherein the positive electrode sheet is obtained by coating a positive electrode slurry on a positive electrode collector and then drying and laminating, and the positive electrode slurry includes a positive electrode active material and a lithium supplement. After packaging and before liquid injection, the preparation method also includes a catalyst preparation step, and the process of the catalyst preparation step includes: sequentially injecting a catalyst precursor solution into the battery cell obtained after packaging, standing treatment, applying current or voltage treatment to the battery cell after standing, and removing the catalyst precursor solution; the process of applying current or voltage treatment to the battery cell after standing causes the catalyst precursor to react and adhere to the surface of the positive electrode sheet to form a catalyst; the above voltage ranges from -2.5 to 0 V.
[0019] The preparation method of the battery cell of the present application, after the battery cell is put into the shell, the catalyst precursor solution is injected after the battery cell is packaged, and the catalyst precursor solution is left to stand so that it can fully infiltrate the positive electrode plate, and then the current or negative voltage (such as -2.5~0 V, further, the negative voltage can be -2.5 V, -2 V, -1.5V, -1.0V, -0.5V or 0 V, but not limited to the listed values, other unlisted values within the numerical range are also applicable) is applied to the battery cell after standing, so that the precursor is directed to move under the action of the electric field force through the applied negative voltage or current, and is reduced (oxidized) and loaded on the surface of the positive electrode plate to form the required catalyst. The catalyst interacts with the lithium supplement agent, and its surface has a certain adsorption energy, which can change the reaction pathway, reduce the reaction activation energy, and then catalyze the lithium delithiation reaction of the lithium supplement agent during the formation, which can not only reduce the lithium delithiation potential window, reduce the decomposition of the electrolyte, but also improve the performance of the battery. Furthermore, the above method of the present application cleverly makes the synthesis process of the catalyst compatible with the preparation process of the battery cell, thereby eliminating the equipment and process for preparing the catalyst separately, thereby simplifying the preparation process of the catalyst and reducing the cost.
[0020] In one embodiment of the present application, the voltage is applied for a time of 0.1 to 12 hours; or, the current density is in the range of 0.5 to 50 mA·cm -2 The time for applying current density is 0.1~12h.
[0021] The time for applying the voltage to the battery cell after standing is controlled within the above range. Preferably, the time for applying the above voltage is 0.1~6h. For example, the time for applying the above voltage is 6min, 10min, 20min, 30min, 45min, 1h, 2h, 3h, 4h, 5h or 6h, but is not limited to the listed values. Other values not listed in the numerical range are also applicable. The preferred time for applying the voltage, the preferred current density and the application time thereof are within the above range, which is more conducive to matching the current or voltage with the potential at which the metal ions in the catalyst precursor solution are reduced, so that the metal ions in the catalyst precursor solution fully and quickly form a catalyst on the surface of the positive electrode. The preferred current density range is 20~50 mA·cm -2 , for example, the current density range is 20 mA·cm -2 , 25 mA·cm -2 、30 mA·cm -2 、35 mA·cm -2 , 40 mA·cm -2 , 45mA·cm -2 or 50 mA·cm -2 , but not limited to the listed values, other values not listed in the numerical range are also applicable. Preferably, the time for applying the current density is 0.1 to 10 hours, for example, the time for applying the current density can be 6 minutes, 10 minutes, 20 minutes, 30 minutes, 45 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours, but not limited to the listed values, other values not listed in the numerical range are also applicable.
[0022] In one embodiment of the present application, compared with the process of packaging, liquid injection and formation of the battery cell after the electrode tab is welded, the process of packaging, catalyst preparation steps, liquid injection and formation of the battery cell after the above-mentioned electrode tab is welded reduces the formation potential window by 0.3~0.8 V.
[0023] Thanks to the electrochemical synthesis method of the above catalyst of the present application, and its compatibility in the preparation process of the battery core, the equipment and process for preparing the catalyst separately are omitted, thereby simplifying the preparation process of the catalyst and reducing the cost, and the catalyst prepared by the above method greatly reduces the potential window of the lithium supplement agent, thereby improving the actual capacity and energy density of the battery. Preferably, the formation potential window is reduced by 0.3~0.55V, for example, the formation potential window is reduced by 0.30V, 0.32V, 0.34V, 0.36V, 0.38V, 0.40V, 0.43V, 0.45V, 0.48V, 0.50V, 0.52V, 0.53V or 0.55V, but not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0024] In one embodiment of the present application, the total molar concentration of the catalyst precursor solution is calculated based on the metal ions in the catalyst precursor solution. .
[0025] The preferred total molar concentration range of the catalyst precursor solution is helpful to form sufficient catalyst on the surface of the positive electrode, thereby reducing the potential window of the lithium supplement agent, so that the lithium supplement agent can release lithium ions at a lower potential, thereby reducing the energy loss of the battery during charging. For example, the total molar concentration of the catalyst precursor solution is 0.1 , 0.2 , 0.3 , 0.4 or 0.5 , but not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0026] In order to promote the release of lithium ions by the lithium supplement agent at low potential as much as possible, thereby improving the overall energy efficiency of the battery, in one embodiment of the present application, the mass ratio of the above-mentioned catalyst to the lithium supplement agent is 1:99~30:70, for example, the mass ratio of the catalyst to the lithium supplement agent is 1:99, 5:95, 10:90, 15:85, 20:80, 25:75 or 30:70, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] In one embodiment of the present application, the mass concentration of the above-mentioned lithium supplement in the positive electrode slurry is 2~3%, and the lithium supplement is preferably selected from any one or more of Li5FeO4, Li2NiO2, Li4SiO4, Li2C4O4, and Li2C2O4.
[0028] The type and content of the above lithium supplement agent preferably within the above range is helpful to fully exert the effect of the lithium supplement agent, so that the battery has a higher capacity and energy density. For example, the mass concentration of the above lithium supplement agent in the positive electrode slurry is 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3%, but is not limited to the listed values, and other values within the numerical range that are not listed are also applicable.
[0029] In one embodiment of the present application, the above-mentioned catalyst precursor solution includes a catalyst precursor and a first solvent, and / or the electrolyte used for injection includes a second solvent; the step of removing the catalyst precursor solution includes: pouring out the catalyst precursor solution remaining after the reaction, and injecting a third solvent into the battery cell to sequentially perform a soaking treatment on the battery cell and a cleaning process of pouring out the solution after the soaking treatment; preferably 2 to 3 cleaning processes are performed, and the time for each soaking treatment is preferably 0.5 to 1 hour; the first solvent, the second solvent and the third solvent are the same type of solvents.
[0030] The preferred above cleaning process and the control of specific washing conditions help reduce the impact of the residual catalyst precursor solution on the performance of the battery cell, wherein the preferred time of each immersion treatment helps to dissolve the catalyst precursor remaining in the battery cell in the immersion liquid as much as possible, for example, the time of each immersion treatment is 0.5h, 0.6h, 0.7h, 0.8h, 0.9h or 1h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. It is preferred that the first solvent, the second solvent and the third solvent are the same type of solvent, which is beneficial to reduce the inevitable impact of the residual catalyst precursor solution on the performance of the battery cell from the source.
[0031] In order to improve the efficiency of converting metal ions in the catalyst precursor into metal catalysts during the electrochemical synthesis process, in one embodiment of the present application, the catalyst precursor is a compound of metal A, and metal A is selected from any one or more of Mo, W, V, Fe, Co, Ni, Mn, Cr, Cu, Zn, Ce, Bi and In; preferably, the compound of metal A is selected from any one or more of metal A halides, metal A nitrates, metal A phosphates, metal A acid salts and metal A complex salts; preferably, the compound of metal A is selected from any one or more of CoCl2, MnCl2, Fe(NO3)3, WCl6, VCl3, Ni(NO3)2 and Li2CuCl4; and / or the compound of metal A is a combination of CoCl2 and MnCl2, and in terms of metal ions, the molar ratio of CoCl2 and MnCl2 is preferably 2:1~5:1, for example, CoCl2 and Mn The molar ratio of Cl2 is 2:1, 3:1, 4:1 or 5:1, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable; and / or the compound of metal A is a combination of Fe(NO3)3 and WCl6, and in terms of metal ions, the molar ratio of Fe(NO3)3 and WCl6 is preferably 2:1~5:1, for example, the molar ratio of Fe(NO3)3 and WCl6 is 2:1, 3:1, 4:1 or 5:1, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable; and / or the compound of metal A is a combination of VCl3 and Ni(NO3)2, and in terms of metal ions, the molar ratio of VCl3 and Ni(NO3)2 is preferably 1:2~1:5, for example, the molar ratio of VCl3 and Ni(NO3)2 is 1:2, 1:3, 1:4 or 1:5, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0032] Further preferred compounds of metal A are a combination of CoCl2 and MnCl2, a combination of Fe(NO3)3 and WCl6, or a combination of VCl3 and Ni(NO3)2, which are more conducive to achieving sufficient synergistic complementarity within the formed catalyst and between the catalyst and the lithium supplement, thereby making the catalyst have a better catalytic effect.
[0033] In one embodiment of the present application, current or voltage is applied to the static cell for multiple times, preferably 2 to 5 times, and the current range of each application is 20 to 50 mA·cm -2 , for example, each applied current is 20 mA·cm -2 、30 mA·cm -2 , 40 mA·cm -2 or 50mA·cm -2, but not limited to the listed values, other unlisted values within the numerical range are equally applicable; the range of each applied voltage is -1.5~0V, for example, each applied voltage is -1.5V, -1V, -0.5V or 0V, but not limited to the listed values, other unlisted values within the numerical range are equally applicable; and / or the temperature of the static treatment is 50~60℃, for example, the temperature of the static treatment is 50℃, 55℃ or 60℃, but not limited to the listed values, other unlisted values within the numerical range are equally applicable; the time of the static treatment is 12~24h, for example, the time of the static treatment is 12h, 14h, 16h, 18h, 20h, 22h or 24h, but not limited to the listed values, other unlisted values within the numerical range are equally applicable.
[0034] Preferably, applying current or voltage treatment to the static battery cell multiple times helps to make the catalyst more evenly distributed on the surface of the positive electrode plate, thereby further helping to improve the efficiency and effect of the catalytic lithium supplement.
[0035] In another typical embodiment of the present application, a battery cell is provided. The battery cell is prepared by the above preparation method.
[0036] The battery cell obtained by the above preparation method has better electrical properties such as actual capacity and energy density.
[0037] The beneficial effects of the present application will be described below in conjunction with specific embodiments and comparative examples.
[0038] Example 1
[0039] After the positive electrode sheet, the negative electrode sheet and the separator are stacked into a laminated battery cell, the laminated battery cell is sequentially subjected to pole ear welding, packaging, liquid injection, formation and vacuum sealing to obtain a battery cell, wherein the positive electrode sheet is obtained by coating the positive electrode slurry on the positive electrode collector and then drying and laminating. The positive electrode slurry includes a positive electrode active material and 0.525 g of a lithium supplement Li2NiO2. The mass concentration of the lithium supplement in the positive electrode slurry is 3%. After packaging and before liquid injection, the preparation method also includes a catalyst preparation step. The process of the catalyst preparation step includes: after the battery cell is shelled, a solution containing 80 mM CoCl2 and 40 mM MnCl2 (the lithium salt in the electrolyte is replaced by a precursor) is injected, and the amount is the same as the injection amount. The lithium supplement is added during the positive electrode homogenization process, and the battery cell is left to stand at 60°C for 12 h. A voltage of -1.5 V is applied to the battery cell for 10 min. The precursor is converted into a catalyst at a negative potential and adheres to the surface of the positive electrode sheet. After electrochemical synthesis, the electrolyte solvent was added and soaked for 3 times, each time for 0.5 h, to remove excess metal ion impurities, and obtain a battery cell with a catalyst attached to the positive electrode sheet. The battery cell with a catalyst attached to the positive electrode sheet was sequentially injected, formed, and evacuated to obtain a battery cell.
[0040] Example 2
[0041] After the positive electrode sheet, the negative electrode sheet and the separator are stacked into a laminated battery cell, the laminated battery cell is sequentially subjected to pole ear welding, packaging, liquid injection, formation and vacuum sealing to obtain a battery cell, wherein the positive electrode sheet is obtained by coating the positive electrode slurry on the positive electrode collector and then drying and laminating. The positive electrode slurry includes a positive electrode active material and 0.525 g of a lithium supplement Li5FeO4. The mass concentration of the lithium supplement in the positive electrode slurry is 3%. After packaging and before liquid injection, the preparation method also includes a catalyst preparation step. The process of the catalyst preparation step includes: after the battery cell is shelled, a solution containing 80 mM Fe(NO3)3 and 40 mM WCl6 (the lithium salt in the electrolyte is replaced by a precursor) is injected. The amount is the same as the amount of liquid injection. The lithium supplement is added during the positive electrode homogenization process, and the battery cell is left to stand at high temperature for 12 hours. A current density of 30 mA cm -2 The precursor was converted into a catalyst at a negative potential after electrochemical synthesis, and then the electrolyte solvent was added and soaked for 3 times, each time for 0.5 h, to remove excess metal ion impurities, and obtain a battery cell with a catalyst attached to the positive electrode. The battery cell with a catalyst attached to the positive electrode was sequentially injected, formed, and vacuum-sealed to obtain a battery cell.
[0042] Example 3
[0043] After the positive electrode sheet, the negative electrode sheet and the separator are stacked into a laminated battery cell, the laminated battery cell is sequentially subjected to pole ear welding, packaging, liquid injection, formation and vacuum sealing to obtain a battery cell, wherein the positive electrode sheet is obtained by coating the positive electrode slurry on the positive electrode current collector and then drying and laminating. The positive electrode slurry includes a positive electrode active material and 0.35 g of a lithium supplement Li5FeO4. The mass concentration of the lithium supplement in the positive electrode slurry is 2%. After packaging and before liquid injection, the preparation method also includes a catalyst preparation step. The process of the catalyst preparation step includes: after the battery cell is shelled, a solution containing 40 mM VCl3 and 80 mM Ni(NO3)2 is injected (the lithium salt in the electrolyte is replaced by a precursor), and the amount used is the same as the amount of liquid injection. The lithium supplement is added during the positive electrode homogenization process, and the battery cell is left to stand at high temperature for 12 hours. The applied current density is 20 mA cm -2 The current density was 20 mA cm-1 for 5 min, and then the current density was 20 mA cm-1. -2 The precursor is converted into a catalyst at a negative potential. After electrochemical synthesis, the electrolyte solvent is added and immersed for 3 times, each time for 0.5 h, to remove excess metal ion impurities, and obtain a battery cell with a catalyst attached to the positive electrode. The battery cell with a catalyst attached to the positive electrode is sequentially injected, formed, and vacuum-sealed to obtain a battery cell.
[0044] Example 4
[0045] After the positive electrode sheet, the negative electrode sheet and the separator are stacked into a laminated battery cell, the laminated battery cell is sequentially subjected to pole ear welding, packaging, liquid injection, formation and vacuum sealing to obtain a battery cell, wherein the positive electrode sheet is obtained by coating the positive electrode slurry on the positive electrode collector and then drying and laminating, the positive electrode slurry includes a positive electrode active material and 0.35 g of a lithium supplement Li2NiO2, the mass concentration of the lithium supplement in the positive electrode slurry is 2%, after packaging and before liquid injection, the preparation method also includes a catalyst preparation step, the process of the catalyst preparation step includes: after the battery cell is shelled, injecting a solution containing 120 mM Li2CuCl4 (the lithium salt in the electrolyte is replaced by a precursor), the amount used is the same as the amount of liquid injection, the lithium supplement is added during the positive electrode homogenization process, standing at high temperature for 12 h, applying a voltage of 1.5 V to the battery cell for 5 min, leaving it for 5 min, and applying 1.5 V again V voltage, the precursor is transformed into a catalyst at a positive potential. After electrochemical synthesis, the electrolyte solvent is added and soaked for 3 times, each time for 0.5 h, to remove excess metal ion impurities, and obtain a battery cell with a catalyst attached to the positive electrode sheet. The battery cell with a catalyst attached to the positive electrode sheet is sequentially injected, formed, and evacuated to obtain a battery cell.
[0046] Example 5
[0047] The difference from Example 1 is that a voltage of 0 V is applied to the battery cell for 2 h, so that the precursor is finally converted into a catalyst under a negative potential and adheres to the surface of the positive electrode sheet to obtain a battery cell.
[0048] Example 6
[0049] The difference from Example 1 is that a solution of 320 mM CoCl2 and 160 mM MnCl2 is used to apply a voltage of -1.5 V to the battery cell for 10 min, so that the precursor is finally converted into a catalyst at a negative potential and adheres to the surface of the positive electrode to obtain a battery cell.
[0050] Example 7
[0051] The difference from Example 1 is that a solution of 52 mM CoCl2 and 26 mM MnCl2 is used to apply a voltage of -1.5 V to the battery cell for 10 min, so that the precursor is finally converted into a catalyst at a negative potential and adheres to the surface of the positive electrode to obtain a battery cell.
[0052] Example 8
[0053] The difference from Example 1 is that a solution of 100 mM CoCl2 and 20 mM MnCl2 is used to apply a voltage of -1.5 V to the battery cell for 10 min, so that the precursor is finally converted into a catalyst at a negative potential and adheres to the surface of the positive electrode to obtain a battery cell.
[0054] Example 9
[0055] The difference from Example 1 is that a solution of 110 mM CoCl2 and 10 mM MnCl2 is used to apply a voltage of -1.5 V to the battery cell for 10 min, so that the precursor is finally converted into a catalyst at a negative potential and adheres to the surface of the positive electrode to obtain a battery cell.
[0056] Example 10
[0057] The difference from Example 2 is that the solution of 100 mM Fe(NO3)3 and 20 mM WCl6 is applied to the cell with a current density of 30 mA·cm -2 The current was applied for 15 min, and finally the precursor was transformed into a catalyst under a negative potential and attached to the surface of the positive electrode to obtain a battery cell.
[0058] Embodiment 11
[0059] The difference from Example 2 is that the solution of 110 mM Fe(NO3)3 and 10 mM WCl6 is applied to the cell with a current density of 30 mA·cm -2 The current was applied for 15 min, and finally the precursor was transformed into a catalyst under a negative potential and attached to the surface of the positive electrode to obtain a battery cell.
[0060] Example 12
[0061] The difference from Example 3 is that the solution of 20 mM VCl3 and 100 mM Ni(NO3)2 applies a current density of 20 mA·cm -2 The current density was 20 mA·cm -2 The current eventually causes the precursor to be transformed into a catalyst at a negative potential and adhere to the surface of the positive electrode to obtain a battery cell.
[0062] Example 13
[0063] The difference from Example 3 is that the solution of 10 mM VCl3 and 110 mM Ni(NO3)2 is used to apply a current density of 20 mA·cm -2 The current density was 20 mA·cm-2 The current eventually causes the precursor to be transformed into a catalyst at a negative potential and adhere to the surface of the positive electrode to obtain a battery cell.
[0064] Embodiment 14
[0065] The difference from Example 2 is that the current density applied to the battery cell is 10 mA·cm -2 The current was applied for 10 h, and finally the precursor was transformed into a catalyst under a negative potential and attached to the surface of the positive electrode to obtain a battery cell.
[0066] Comparative Example 1
[0067] The difference from Example 1 is that after packaging and before liquid injection, there is no catalyst precursor solution injection step to obtain a battery cell.
[0068] The voltage windows during the formation process of the above embodiments and comparative examples were recorded, and the first charge gram capacity of the battery cells obtained in the above embodiments and comparative examples at 0.01 C was tested, and the test results are listed in Table 1.
[0069] Table 1
[0070]
[0071] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0072] The preparation method of the battery cell of the present application, after the battery cell is put into the shell, the catalyst precursor solution is injected after the battery cell is packaged, and the catalyst precursor solution is left to stand so that it can fully infiltrate the positive electrode plate, and then the current or negative voltage (such as -2.5~0 V, further, the negative voltage can be -2.5 V, -2 V, -1.5V, -1.0V, -0.5V or 0 V, but not limited to the listed values, other unlisted values within the numerical range are also applicable) is applied to the battery cell after standing, so that the precursor is directed to move under the action of the electric field force through the applied negative voltage or current, and is reduced (oxidized) and loaded on the surface of the positive electrode plate to form the required catalyst. The catalyst interacts with the lithium supplement agent, and its surface has a certain adsorption energy, which can change the reaction pathway, reduce the reaction activation energy, and then catalyze the lithium delithiation reaction of the lithium supplement agent during the formation, which can not only reduce the lithium delithiation potential window, reduce the decomposition of the electrolyte, but also improve the performance of the battery. Furthermore, the above method of the present application cleverly makes the synthesis process of the catalyst compatible with the preparation process of the battery cell, thereby eliminating the equipment and process for preparing the catalyst separately, thereby simplifying the preparation process of the catalyst and reducing the cost.
[0073] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a battery cell, comprising: After the positive electrode sheet, the negative electrode sheet and the separator are stacked into a stacked battery cell, the stacked battery cell is sequentially subjected to pole ear welding, packaging, liquid injection, formation and vacuum sealing to obtain a battery cell, wherein the positive electrode sheet is obtained by coating the positive electrode slurry on the positive electrode collector, drying and laminating, and the positive electrode slurry includes a positive electrode active material and a lithium supplement agent, characterized in that after the packaging and before the liquid injection, the preparation method further includes a catalyst preparation step, and the process of the catalyst preparation step includes: Injecting a catalyst precursor solution into the cell obtained after packaging, placing the cell in a static state, applying a current or voltage treatment to the cell after the static state, and removing the catalyst precursor solution in sequence; The process of applying current or voltage treatment to the static cell allows the catalyst precursor to react and adhere to the surface of the positive electrode plate to form a catalyst; The voltage range is -2.5~0 V; The lithium supplement agent is selected from any one or more of Li5FeO4, Li2NiO2, Li4SiO4, Li2C4O4, and Li2C2O4; The catalyst precursor solution includes a catalyst precursor and a first solvent, wherein the catalyst precursor is a compound of metal A, and the metal A is selected from any one or more of Mo, W, V, Fe, Co, Ni, Mn, Cr, Cu, Zn, Ce, Bi and In.
2. The preparation method according to claim 1, characterized in that: The voltage is applied for a period of 0.1 to 12 h; or the current density is in the range of 0.5 to 50 mA·cm -2 The time for applying the current density is 0.1~12h.
3. The preparation method according to claim 1, characterized in that: Compared with the process of packaging, injecting and forming the battery cell in sequence after the tab welding, the process of packaging, catalyst preparation, injecting and forming the battery cell in sequence after the tab welding reduces the formation potential window by 0.3~0.8V.
4. The preparation method according to any one of claims 1 to 3, characterized in that The total molar concentration of the catalyst precursor solution is 0.1-0.5 mol∙L based on the metal ions in the catalyst precursor solution. -1 .
5. The preparation method according to any one of claims 1 to 3, characterized in that: The mass ratio of the catalyst to the lithium supplement agent is 1:99 to 30:
70.
6. The preparation method according to any one of claims 1 to 3, characterized in that: The mass concentration of the lithium supplement agent in the positive electrode slurry is 2-3%.
7. The preparation method according to any one of claims 1 to 3, characterized in that The electrolyte used for the injection includes a second solvent; The steps of removing the catalyst precursor solution include: The catalyst precursor solution remaining after the reaction is poured out, and a third solvent is injected into the battery cell to sequentially perform a soaking treatment on the battery cell and a cleaning process of pouring out the solution after the soaking treatment; The cleaning process is performed 2 to 3 times, and the soaking time of each treatment is 0.5 to 1 hour; The first solvent, the second solvent and the third solvent are the same type of solvents.
8. The preparation method according to any one of claims 1 to 3, characterized in that: The compound of metal A is selected from any one or more of metal A halides, metal A nitrates, metal A phosphates and metal A complex salts.
9. The preparation method according to any one of claims 1 to 3, characterized in that: The compound of metal A is selected from any one or more of CoCl2, MnCl2, Fe(NO3)3, WCl6, VCl3, Ni(NO3)2 and Li2CuCl4.
10. The preparation method according to claim 9, characterized in that: The compound of the metal A is a combination of CoCl2 and MnCl2, and the molar ratio of the CoCl2 to the MnCl2 is 2:1 to 5:1 based on metal ions.
11. The preparation method according to claim 9, characterized in that: The compound of the metal A is a combination of Fe(NO3)3 and WCl6. The molar ratio of the Fe(NO3)3 to the WCl6 is 2:1 to 5:1 based on metal ions.
12. The preparation method according to claim 9, characterized in that: The compound of the metal A is a combination of VCl3 and Ni(NO3)2, and the molar ratio of the VCl3 to the Ni(NO3)2 is 1:2-1:5 based on metal ions.
13. The preparation method according to any one of claims 1 to 3, characterized in that: Apply current or voltage to the rested cells for multiple times. The number of times of applying current or voltage is 2 to 5 times. The current range of each application is 20 to 50 mA cm -2 , the range of each applied voltage is -1.5~0 V; And / or the temperature of the static treatment is 50-60° C., and the time of the static treatment is 12-24 h.
14. A battery cell, characterized in that: The battery cell is prepared by the preparation method described in any one of claims 1 to 13.
Citation Information
Patent Citations
Lithium-ion secondary battery, and preparation method therefor, battery module, battery pack, and device
US20230282824A1
Initial charging and capacity verification method for lithium-ion battery containing positive electrode lithium supplementation additive
WO2024193319A1